ANALISIS PERHITUNGAN PAJAK PENGHASILAN KARYAWAN (PPh) PASAL 21 PADA PT. UNTUNG BRAWIJAYA SEJAHTERA SAMARINDA - Andi Indrawati 3, Novia Paramita 1, Mardiana 2, (EKONOMIA, 2020)
Tax Article 21At  PT.  Untung  Brawijaya  Sejahtera  Samarinda  (under  the  guidance  of     Mrs. Mardiana as supervisor I and Andi Indrawati as supervisor II).This study aims to analyze and find out the tax calculation of the employees of PT. Untung Brawijaya Sejahtera Samarinda is in accordance with the  provisions of Income  Tax Article 21  of Law Number  36 Year 2008  and Regulation  of  the Minister of Finance Number 101 / PMK.010 / 2016.The theory used in this research is tax accounting which focuses on income tax article 21 at PT. Untung Brawijaya Sejahtera Samarinda.The analytical tool used is comparative, which compares employee income tax and disclosures based on Income Tax Article 21 of Law Number 36 Year 2008 and Minister of Finance Regulation Number 101 / PMK.010 / 2016.The results showed that the employee income tax with permanent employee status that has a Taxpayer Identification Number (NPWP) is in conformity and employee income tax with permanent employee status that does not have a Taxpayer Identification Number (NPWP) not in accordance with the provisions of Income Tax article 21 of the Law Number 36 Year 2008 and Regulation of the Minister of Finance Number 101 / PMK.010 / 2016.